THE ACADEMIC ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN CORRECTING WORSHIP MISCONCEPTIONS AT SMP NEGERI 14 MERANGIN - Violita Rahmadani; Najmul Hayat (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
This study examines the academic role of Islamic Religious Education (IRE) teachers in addressing students’ misconceptions in worship at SMP Negeri 14 Merangin. Using a qualitative descriptive approach, data were collected through observations, interviews, and documentation from teachers and students. Findings reveal students struggle with understanding obligatory (wajib) and recommended (sunnah) worship due to internal factors such as low understanding and interest, and external factors including teaching methods and limited instructional media. Teachers play a critical role in identifying misconceptions, providing re-explanations, applying varied teaching methods, guiding students, and evaluating learning. The study underscores the importance of systematic pedagogical strategies to improve students’ religious understanding.